2015
DOI: 10.17159/2413-3221/2015/v43n2a344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Information Communication Technology (ICT) on agricultural information access among extension officers in North West Province South Africa

Abstract: This study determined the effect of Information Communication Technology (ICT) on agricultural information access among extension officers in North West Province South Africa. A simple random sampling technique was used to select 169 officers from which data were collected with structured and face validated questionnaire. Fourteen statements were perceived by officers as having an effect on improving information access. Significant determinants of the effect of ICT on information access were education (t= 2.61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 3 publications
2
28
0
1
Order By: Relevance
“…The results from Table 2 also reveal that slightly above half (58.1% and 52.7%) of the public and private agents had a rural background, that they were born and brought-up in the rural area. Oladele (2015) also reported that approximately half of the extension officers in North West Province, South Africa have a rural background. Table 3 shows that majority (79.3%) of the extension agents across the study area had a wide range of knowledge regarding professionalization (12 statements).…”
Section: Socio-economic Characteristics Of the Extension Agentsmentioning
confidence: 99%
“…The results from Table 2 also reveal that slightly above half (58.1% and 52.7%) of the public and private agents had a rural background, that they were born and brought-up in the rural area. Oladele (2015) also reported that approximately half of the extension officers in North West Province, South Africa have a rural background. Table 3 shows that majority (79.3%) of the extension agents across the study area had a wide range of knowledge regarding professionalization (12 statements).…”
Section: Socio-economic Characteristics Of the Extension Agentsmentioning
confidence: 99%
“…Findings from this study agree with studies conducted elsewhere that farmers received information on mobile phones (Chhachhar et al, 2014;Chhachhar & Hassan, 2013;Martin & Abbott, 2008;Mwakaje, 2010;Nyamba & Mlozi, 2012;Tadesse & Bahiigwa, 2015) that enabled them to make informed decisions (Nyamba & Mlozi, 2012;Tadesse & Bahiigwa, 2015), got better market prices (Mwakaje, 2010), weather information (Nyamba & Mlozi, 2012), saved time and transport costs by overcoming geographical distances through voice calls and text messaging (Deloitte, 2012;Nyamba & Mlozi, 2012) consulted agriculture extension staff or advisors (Martin & Abbott, 2008;Oladele, 2015) and utilized mobile financial transactions (Deloitte, 2012;Nyamba & Mlozi, 2012). The use of other mobile phone applications like internet and WhatsApp were reasonable for rural population.…”
Section: Current Use Of Mobile Phones In Agriculture In the Svosve-wementioning
confidence: 99%
“…According to Technomag (2014) mobile phone subscription in the rural population was 63% in 2013. Mobile technology can potentially transform all forms of business including agriculture (Jensen, 2001;Deloitte, 2012;Irefin, Abdu-Azeez & Tijani, 2012;World Bank, 2012;Ewing et al, 2014;Oladele, 2015). Traditionally, communication in rural Zimbabwe has always been limited but mobile ICT has significantly connected these areas to others locally, regionally and internationally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The philosophy and rationale of the extension services have been changed and is shifting towards participatory development and development towards extension plus i.e. the extension and advisory services (Oladele, 2015).…”
Section: Introductionmentioning
confidence: 99%